2016
DOI: 10.1038/cddis.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Low nanomolar concentrations of Cucurbitacin-I induces G2/M phase arrest and apoptosis by perturbing redox homeostasis in gastric cancer cells in vitro and in vivo

Abstract: Cucurbitacin-I (Cu-I, also known as Elatericin B or JSI-124) is developed to inhibit constitutive and abnormal activation of STAT3 in many cancers, demonstrating a potent anticancer activity by targeting disruption of STAT3 function. Here, we for the first time systematically studied the underlying molecular mechanisms of Cu-I-induced gastric cancer cell death both in vitro and in vivo. In our study, we show that Cu-I markedly inhibits gastric cancer cell growth by inducing G2/M phase cell cycle arrest and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
3
28
1
Order By: Relevance
“…7,8 As one of the 12 categories of cucurbitacins, cucurbitacin-I shows a potent anticancer effect on several types of cancer cells, including breast cancer, lung cancer, and glioma. [9][10][11][12][13] Cucurbitacin-I performs its anticancer action through the inhibition of JAK/ STAT3, PI3K/AKT/p70S6K, or PAK1/PAK4 signaling pathways, as well as the modulation of the balance between autophagic and apoptotic modes of cancer cell death. In fact, the molecular and cellular mechanisms underlying the induction of cucurbitacin-I in tumor cell death are very complex, which deserves further study.…”
mentioning
confidence: 99%
“…7,8 As one of the 12 categories of cucurbitacins, cucurbitacin-I shows a potent anticancer effect on several types of cancer cells, including breast cancer, lung cancer, and glioma. [9][10][11][12][13] Cucurbitacin-I performs its anticancer action through the inhibition of JAK/ STAT3, PI3K/AKT/p70S6K, or PAK1/PAK4 signaling pathways, as well as the modulation of the balance between autophagic and apoptotic modes of cancer cell death. In fact, the molecular and cellular mechanisms underlying the induction of cucurbitacin-I in tumor cell death are very complex, which deserves further study.…”
mentioning
confidence: 99%
“…GADD45α is a well‐known p53‐responsive stress protein to repair DNA damage, induce G2/M cell cycle arrest and apoptosis in various cancer cells . Recently we have demonstrated that GADD45α can be induced by Cucurbitacin‐I through a p53‐independent manner and associated with G2/M cell cycle arrest and apoptosis in gastric cancer cells . Earlier studies have revealed that GADD45α was downregulated in HCC cells, and its ectopic expression led to G2/M arrest .…”
Section: Discussionmentioning
confidence: 99%
“…siRNAs target UBE2Q1 and GADD45α as well as a negative control siRNA (sequences are detailed in Supplementary Table S1) were purchased from Invitrogen (Carlsbad, CA). Transfection was carried out using Lipofectamine RNAiMax Reagent (Invitrogen) as described previously . Lentivirus plasmid vectors pLKO.1‐puro vectors containing shRNA targeting UBE2Q1 (TRCN0000004205) and pLKO.1‐puro lentiviral vector expressing a non‐targeting shRNA was used to establish the stable cell line.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations